RESPONSE OF POD NUTRIENT CONTENT AND YIELD OF OKRA TO APPLICATION OF SOLE AND AMENDED PLANT RESIDUES - Ojeniyi, S. O.; Folorunso, O. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A study was conducted to determine the effect of wood ash, sawdust, ground cocoa pad husk, spent grain and rice bran, used ordinarily or amended with goat, pig and poultry manure on pod nutrient content and yield of okra (Abelmochus esculentus (L.) Moench). The twenty organic fertilizer treatments were compared with the control and 400 kg/ha NPK fertilizer in four field experiments. Application of sole and amended 6t/ha plant residue to soil increased pad N, P, K, Ca and Mg content and pod count. Wood ash was most effective in improving pod nutrient content and pod count, whereas rice bran and sawdust were least effective. Amendment of plant residues with animal manure tended to improve the effectiveness of the plant residues on pod N and P status and count. Compared to NPK fertilizer, plant residues increased pod Ca and Mg content and pod count. Relative to the control, NPK fertilizer, wood ash, cocoa husk, rice bran, spent grain and sawdust increased pod count by 79,385, 168, 115, 230 and 185% respectively.